Investigation of dietary factors in migraineurs. - Li, Hongjin; Zhang, Yingbo; Li, Qiang; Li, Yingying; Diao, Xiaojun; Chen, Chunfu (Investigación Clínica, 2020)
Abstract. We conducted the current study to investigate migraine-related dietary factors in migraine patients. Seventy patients with migraine and 30 patients with tension-type headache were enrolled in the study, recruited from the headache outpatient department of the Shandong Provincial Hospital from June 2014 to May 2016. The average age of the migraine group was 15 to 60 years with an average of 35.5 ± 13.8 years, including 23 males and 47 females (1: 2.04 male to female ratio). The age of patients with tension-type headache ranged from 18 to 60 years-old with an average of 35.4 ± 14.4 years, including 13 males and 17 females (1: 1.31 male to female ratio). The headache was graded based on the severity and frequency of the episodes, according to the ICHD-II diagnostic criteria, during symptom intermission. The results were analyzed with the SPSS 21.0 software. Thirty migraine patients (42.9%) and three tension-type headache patients (10.0%) presented diet-induced factors. There was a significant difference (p<0.05). The difference in rates of foodinduced factors between migraine patients with aura and migraine patients without aura was statistically significant (p<0.05), and food-induced factors are more common in migraine patients with aura. The most common foodinduced factor in males was alcohol while the food-induced factors in female varied more. Both, the headache frequency and severity in migraine patients with food-induced factors, were higher than those in migraine patients without food-induced factors (p<0.05), but the difference in the headache duration was not statistically significant (p>0.05). Resumen. El estudio se realizó para investigar los factores alimentarios relacionados con la migraña en los pacientes que sufren este trastorno. Se escogieron 70 casos de migrañas y 30 casos de cefaleas de tipo tensional, entre junio de 2014 y mayo de 2016, reclutados de la Clínica de Jaqueca del hospital provincial de Shandong. La edad media de los grupos de migrañas osciló entre los 15 y los 60 años, con un promedio de 35,5 ± 13,8 años, de los cuales 23 fueron hombres y 47 mujeres (1: 2,04 ratio). Los casos de cefalea de tipo tensional tenían entre 18 y 60 años, con un promedio de 35,4 ± 14,4 años, de los cuales 13 eran hombres y 17 mujeres (1: 1,31 ratio). Los dolores de cabeza se clasificaron en función de la gravedad y la frecuencia con arreglo a los criterios de diagnóstico del ICHD - II para el intervalo sintomático. Los resultados se analizaron con el programa informático SPSS 21.0. Se encontraron factores alimentarios inductores en 30 casos de migraña (42,9%) y en tres casos de cefalea de tipo tensional (10,0%). La diferencia fue significativa (p<0,05). Hubo una diferencia estadísticamente significativa entre la incidencia de los factores inductores alimentarios entre las personas con migrañas con aura y las personas con migrañas sin aura (p<0,05). Estos factores fueron más comunes entre las personas que presentaban migrañas con aura. El factor alimentario inductor más común entre los hombres fue el alcohol, mientras que en las mujeres fue más variable. Tanto la frecuencia de la cefalea como su severidad, fueron mayores en pacientes con migraña con factores alimentarios inductores que en pacientes sin estos factores inductores (p<0,05), pero la diferencia en la duración de la cefalea no fue estadísticamente significativa (p>0,05).